Synthesis and characterization of alkali-activated loess and its application as protective coating. (3rd May 2021) - Dassekpo, Jean-Baptiste Mawulé; Feng, Weipeng; Li, Yanru; Miao, Lixin; Dong, Zhijun; Ye, Jianqiao
Graphical abstract: Highlights: Alkali-activation and application of loess mortars were studied. Alkali-activators have significant effects on loess geopolymers. Loess coating applied to concrete exhibited best performances. New ways of recycling loess into useful and sustainable materials. Abstract: Environmental friendly and sustainable repair materials with reduced carbon emission have been in high demand worldwide. Frequent deterioration of cement concrete structures is unpreventable and requires appropriate repair materials. Aside from the cementitious, polymeric or resinous materials used to remedy this problem, geopolymeric mortars are reported to be friendly and more sustainable, considering the lower energy required for its production and its intrinsic properties. When selecting geopolymer produced from aluminosilicate waste as repair materials, a measured dissolution in an adequate alkaline solution is required for geopolymerization. Accordingly, this paper examines the synthesis and properties of alkali-activated loess, followed by its effective application as concrete protective coating. The geopolymer mortars (GPMs) were made from loess and ground granulated blast slag (GGBS), and activated with either sodium hydroxide or a combination of sodium hydroxide and sodium silicate solutions. Experimental results showed that, both alkali activators have major influences on the apparent viscosity, roughness, compressibility and microstructural properties of loess GPMs. Results from nanoindentation also reveal good adhesion, higher bulk indent modulus and hardness of the applied mortar, a fact that makes loess geopolymer a great potential repair material to be used as barrier coating for cement concrete substrates.